Abadeha the Philippine Cinderella - De La Paz, Myrna J.; Tang, Youshang (Auburn, Calif. Shen's Books, 2001)
In this version of Cinderella, set in the Philippines, Abadeha endures abuse by her stepmother before being helped by the Spirit of the Forest and becoming the bride of the island chieftan's son.
Title from cover.
Keywords: Folklore -- Philippines; Fairy tales